ภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสำนักเรียนพระปริยัติธรรมแผนกบาลีในเขต ปกครองคณะสงฆ์ หนกลาง - ชุติมนฺตี, พระมหาช่วง (วารสาร ศึกษาศาสตร์ มมร, 2016)
วิทยานิพนธ์นี้มีวัตถุประสงค์เพื่อศึกษาภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสำนักเรียน และเพื่อยืนยันภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสำนักเรียนพระปริยัติธรรมแผนกบาลี ในเขตปกครองคณะสงฆ์ หนกลาง ประชากรคือ ผู้บริหารสำนักเรียนพระปริยัติธรรม จำนวน 8 รูป และผู้เชี่ยวชาญด้านภาวะผู้นำเชิงสร้างสรรค์ จำนวน 10 ท่าน และกลุ่มผู้เชี่ยวชาญจากผู้บริหารสำนักเรียน 10 รูป เป็นการวิจัยเชิงคุณภาพ โดยการใช้เทคนิคการวิจัยเชิงอนาคตแบบชาติพรรณวรรณนา (EFR) เครื่องมือที่ใช้ในการวิจัยเป็นแบบสัมภาษณ์ชนิดปลายเปิด ร่วมกับการใช้เทคนิคการวิจัยแบบสนทนากลุ่ม และแบบยืนยันภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหาร การวิเคราะห์ข้อมูลใช้วิธีการวิเคราะห์เนื้อหา โดยกลั่นกรองให้เกิดมุมมองภาพอนาคตที่เป็นไปได้มากที่สุด ผลการวิจัยพบว่า 1) ภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหาร ประกอบด้วย 4 ด้าน คือด้านพฤติกรรม ด้านสติปัญญา ด้านวิสัยทัศน์ และด้านการบริหารจัดการ 2) ภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารมีความเหมาะสม ความเป็นไปได้ความถูกต้อง และการนำไปใช้ประโยชน์ได้ แนวทางการส่งเสริมภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสำนักเรียนพระปริยัติแผนกบาลี ในเขตปกครองคณะสงฆ์หนกลาง ควรมีองค์ประกอบอื่น  ๆ เช่น การบริหารการเปลี่ยนแปลง การบริหารที่ยึดวัตถุประสงค์ เป็นต้น แล้วควรมีความชัดเจน ปฏิบัติได้จริง เป็นรูปธรรม มีการประสานภารกิจของสำนักเรียนอย่างสอดคล้องกันทั้งระบบ มีเป้าหมายของสำนักเรียนชัดเจน ABSTRACT The purposes of this study were to study the creative leadership of administrators and confirm the creative leadership of administrators in the Phrapariyattidhamma School on Pali section section of Sangha Central region. The population consists of eight administrators in the Phrapariyattidhamma School on Pali section, and ten creative leadership administrative experts in the Phrapariyattidhamma School on Pali section. This study is qualitative research in research design of Ethnographic Future Research (EFR). The research instruments were used in this study is open - ended interviews, focus group discussion, and conformatio nal form of the creative leadership of administrators in the Phrapariyattidhamma School on Pali section of Sangha. The technique for data analysis is content analysis for filtering the idea, and the possible view in the future. The results of the research were as follows: 1) The Creative leadership of administrators in the Phrapariyattidhamma school on Pali section section of Sangha Central region consists of four factors, that is, behavioral, cognitive, vision, and management because it comprises the action, knowledge, vision and efficient management.  2) The Creative leadership of Administrators in the Phrapariyattidhamma school on Pali section section of Sangha Central region is appropriate, feasible, accurate, and utilizable at the maximum level. The guidelines for supporting the Creative leadership of Administrators in the Phrapariyattidhamma school on Pali section section of Sangha Central region are very well and appropriate format but it should have other elements corresponding to modern management system. It is not only four factors but also the dimension of change management and objective management. Quality and effective will be good. The characters of administrators in the Phrapariyattidhamma school on Pali section who will success in their work should consist of clarity, acceptation of the members, understanding the corporate culture and tradition, integration of systematical school mission, and clear goal of administrative process.